How do commitment-based HRM practices and a developmental culture interact to foster open innovation in SMEs? - Elona Cera; Roland Subashi (Problems and Perspectives in Management, 2024)
This paper aims to bring new insights into the role of commitment-based human resource management practices in open innovation in small and medium-sized enterprises. Additionally, the goal is to enhance comprehension of the aforementioned interactions by considering the mediating effect of developmental culture. Data were collected from owners and managers of 131 small and medium-sized enterprises operating in the service and manufacturing sectors in Albania. The study employed a quantitative research instrument, namely online surveys. To yield results and extract figures, the study applied partial least squares-structural equation modeling, examining the interrelationships among constructs. The empirical results highlight the direct effects of commitment-based human resource management practices and developmental culture on open innovation. Specifically, the study reveals that commitment-based human resource management practices have a significant role in promoting open innovation (O = 0.598, t = 10.057, p = 0.000). Additionally, the findings indicate that developmental culture serves as a complementary factor by mediating the connection between commitment-based human resource management practices and open innovation (O = 0.136, t = 1.789, p = 0.037). This study draws the attention of business owners and strategy developers circumnavigating the Albanian small and medium-sized enterprises environment. Barring certain limitations, it enthralls their propensity toward innovation, aligning it with an enabling business culture. AcknowledgmentThis work is supported by Tomas Bata University internal grants, FaME TBU No. IGA/FaME/2023/012 “Closed and open innovation: role of human resource, servant leadership, digitalization, and uncertainty.”